Metodologia de cálculo da margem de transmissão visando subsidiar leilões de energia - Lima, Sérgio Felipe Falcão (2019)
Some types of energy auction utilise the concept of remaining transmission margin in order to coordinate the contracted generation with the existing grid on the date of the initial energy delivery. These auctions impose limits to the contracted energy according to the availability flow capacity of the electric grid. Thus, such auctions mitigate the gap between recommended transmission facilities to accommodate the additional generation into the electric system, in a framework of uncertainties regarding the location of future generations, especially when considering alternative sources. This work discusses the constraints involved in the transmission margin calculation, proposes and applies a methodology based on a probabilistic approach, low expectation generation curtailment metrics, AC power flow and optimization techniques, considering a large number of hourly operation scenarios. Firstly, the remaining margin results are obtained through the application of the proposed methodology in both a test and a large-scale system and compared with the classic reduced scenario and conservative metrics approach. Lastly, an auction protocol is performed, in which the margin results obtained in the first step are used as grid constraints. The results reveal the likelihood of buying cheaper and competitive sources in electrical system nodes with high quality energy resources, due to possible increases of remaining transmission margins, while a reliable and adequate operation of the transmission network is preserved.